“Heaven Came Down to Earth When No One Expected It”: Reassessing Seven Christological Titles in Light of Insights from Contemporary Jewish-Christian Conversations - Svartvik, Jesper (Studies in Christian-Jewish Relations, 2026)
This article seeks to further intra-Christian theological reflection and contemporary Jewish-Christian dialogue by surveying seven Christological terms that frequently appear in the New Testament and Christian discourse: Rabbi, Christ / Messiah, Son of God, Son of Man, Lord, Wisdom, and Word of God. What is particularly striking is that these Christological terms are far from monolithic; they are surprisingly multifaceted. Indeed, they are even ambiguous and enigmatic, inviting readers of the New Testament to reflect on one of the most important questions for Christians (Matt 16:15, Mark 8:29, and Luke 9:20): “Who do you say that I am?” The article concludes with several ensuing implications for Jewish-Christian dialogue and Christology, ending with the question, will Christians choose a triumphalist or a servant Christology?